Polarization in the lossy mode resonance sensor based on directly drawn D-shape fiber - Kasztelanic, Rafał; Stepniewski, Grzegorz; Pysz, Dariusz; Buczynski, Ryszard (Photonics Letters of Poland, 2024)
Standard fiber optic sensors based on D-shape fibers are typically fabricated from step-index fibers with a circular core. Such fibers do not maintain polarization, so unpolarized light is used in measurements. However, a new method based on the direct drawing of a modified preform has been developed, resulting in a fiber with an elliptical core. This innovative approach not only offers a fiber that maintains a polarized state but also opens up exciting possibilities for enhancing the performance of optical fiber sensors based on Lossy Mode Resonance. Full Text: PDF References A. K. Sharma, J. Gupta, J Sharma, "Fiber optic evanescent wave absorption-based sensors: A detailed review of advancements in the last decade (2007–18)", Optik 183, 1008 (2019). CrossRef S. Pissadakis, "Lab-in-a-fiber sensors: A review", Microelectronic Engineering 217, 111105 (2019). CrossRef Y. Yinga, G. Sib, F. Luana, K. Xua, Y. Qia, H. Li, "Recent research progress of optical fiber sensors based on D-shaped structure", Optics & Laser Technology 90, 149 (2017). CrossRef M. Piliarik, J. Homola, "Surface plasmon resonance (SPR) sensors: approaching their limits?", Opt. Express 17, 16505 (2009). CrossRef F. Yang, J. R. Sambles, "Determination of the optical permittivity and thickness of absorbing films using long range modes", J. Mod. Opt. 44, 1155 (1997). CrossRef F. Chiavaioli, D. Janner, "Fiber Optic Sensing With Lossy Mode Resonances: Applications and Perspectives", J. Lightwave Technology 39(12), 3855 (2021). CrossRef G. Stepniewski, A. Filipkowski, D. Pysz, J. Warszewski, R. Buczynski, M. Smietana, R. Kasztelanic, "From D-shaped to D-shape optical fiber – A universal solution for sensing and biosensing applications: Drawn D-shape fiber and its sensing applications", Measurement 222, 113642 (2023). CrossRef